Public limited company versus limited liability company. A comparative vision (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2019)
This essay offers an analysis between the public limited company and the limited liability company regulated by the Venezuelan Commercial Code, for which an exhaustive study was made based on the provisions contained in the commercial code, documents, national jurisprudence and literary productions. related to commercial companies, in order to determine, through the use of the comparative method, their coincidental and differential aspects, starting from ten tables referring to their characteristic elements: the signature, the social capital, the responsibility of the partners, the form of constitution, the administrators, the commissioner, the assemblies, the legal reserve, the dissolution and the liquidation, whose contrast grants a precise vision to the study of such societies. It was concluded that both companies maintain common characteristics and regulations, allowing the SRL to be classified as a capital company; and within those in which there is variation, the main differentiating gene is found in the form of capital; It was also established that the CA enjoys an organization well determined by the commercial legislator, as it has three (3) clearly defined bodies, a decision-making body called Assemblies, one management represented by the Administrators and a control body expressed in the Commissar; in the SRL, this is not the case, the existence of the decision-making body depends on the will of the partners and the control body of the amount of the share capital; which is why, in practice, one could find one with an incomplete social structure in its bylaws
Keywords: limited company; limited liability; comparative vision